Regulation of intergovernmental relations in the socio-economic development of regions of Ukraine - Булеца, Надія Володимирівна (Technology audit and production reserves, 2016)
The features of the regulatory support of the budget regulation of the social and economic development of regions of Ukraine have been considered in the article. The necessity of such justification has been caused by current changes in tax and budget legislation of Ukraine in the context of European integration. It was determined that the features of the tax and budget legislation of Ukraine which have been caused by the necessity of problem solution of the organization of inter-budget relations from a perspective of financial support of regions are the legislation improvement within the frame of decentralization, the significant extension of community power, the extension of filling sources of resource base of the local budget. The main strategic directions of social and economic development of Ukraine, among which the implementation of effective tools of budget regulation of such development is important, have been determined. Attained results allow to define the main principles of inter-budget relations regulation as a security of social and economic development of regions of Ukraine from a perspective of the contribution of their financial support.